TECHNICAL SRATEGY IN ADDRESSING THE PERCEPTION AND PARTICIPATION OF THE SOCIETY ON HEAVY METAL POLLUTION IN NGIPIK LAKE KEBOMAS GRESIK - Aliyah, Ummu; Hariyadi, Mohammad (Tibuana, 2020)
Cadmium (Cd) is one type of heavymetals that is harmful because these elementsare at high risk of blood vessels, cadmiumaffects humans over long periods of time andcan accumulate in the body especially theliver and kidneys, Some researchers haveproved the contamination of heavy metalsoccurring in Ngipik Lake, so that is feared isthe human body exposure to environmentalpollution caused by consuming fish from thispond. Telaga Ngipik , originally a formerclay mine land owned by PT. Semen Gresik.The land area of 2,250 M2 that has beenexploited the mining of lime material for rawmaterials was dredged and left the puddle orhole that turned into a lake. Through theenvironmental development Program of PT.Semen Gresik, this lake has turned into atourist attraction for local residents, but alsoused as fishing place, children's play area,water ski, as well as raw materials fordrinking water. Perda No. 10 tahun 2010 ongreen Open Space arrangement has set upTelaga Ngipik including the Green Line ofLake borders. It was further strengthened inthe P2KH (Green City developmentProgram) to set up a green open spacestarting from 2012 where the management ofthis green open space involved thecommunity and private participation in theRAKH (Green City Action Plan).